The Effect of Corporate Life Cycle on Corporate Restructuring - Sari, Nur Afiqoh (Universitas Muhammadiyah Surakarta, 2022)
This study aims to determine the effect of corporate life cycle on restructuring decisions with governance and financial distress as moderating variables in manufacturing companies listed on the Indonesia Stock Exchange in five years (2013- 2017) and there are 480 data for the sample. The hypotheses tested using logistic regression. The results of this study indicate that life cycle has an effect on restructuring decisions. Financial distress strengthen the influence of the “birth” and “mature” stages to carry out managerial restructuring, and strengthen the “growth” stage to carry out operational restructuring and financial restructuring. However, financial distress does not moderate the influence of the life cycle on asset restructuring. Governance weakens the influence of the “birth” stage in managerial restructuring and also weakens the influence of the “birth” and “mature” stages in financial restructuring strategies. GCG does not moderate the effect of the life cycle on operational restructuring and asset restructuring.